2005
DOI: 10.1007/s00251-005-0058-1
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate-binding specificities of mouse ficolin A, a splicing variant of ficolin A and ficolin B and their complex formation with MASP-2 and sMAP

Abstract: Ficolins are a group of proteins mainly consisting of collagen-like and fibrinogen-like domains and are thought to play a role in innate immunity via their carbohydrate-binding activities. Two types of ficolins have been identified in mice, ficolin A, and ficolin B. However, their structure and function are not fully understood. In this study, we isolated the cDNA encoding a novel variant of ficolin A having a shorter collagen-like domain and a longer gap sequence, which was generated from the ficolin A gene b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(58 citation statements)
references
References 36 publications
3
53
0
Order By: Relevance
“…It is reasonable that sMAP also regulates another route of the lectin pathway activated by the ficolin-MASP complex. MASP-2 and sMAP also competed to bind mouse ficolin A and down-regulate the C4 cleavage activity of the ficolin A-MASP complex (37). A study of MBL null mice was recently reported (38).…”
Section: Discussionmentioning
confidence: 97%
“…It is reasonable that sMAP also regulates another route of the lectin pathway activated by the ficolin-MASP complex. MASP-2 and sMAP also competed to bind mouse ficolin A and down-regulate the C4 cleavage activity of the ficolin A-MASP complex (37). A study of MBL null mice was recently reported (38).…”
Section: Discussionmentioning
confidence: 97%
“…Recombinant FcnA (rFcnA) was prepared by using a Drosophila expression system with the pMT/Bip/V5-His A vector (Invitrogen, Carlsbad, CA) as previously described (25). Recombinant FcnB (rFcnB) was produced in the Chinese hamster ovary cells using a piggyBac transposon-mediated gene expression system: cotransfection with mouse FcnB cDNA-containing pIRCMV plasmid and pFerH plasmid.…”
Section: Recombinant Lectinsmentioning
confidence: 99%
“…C4-deposition assay was used to evaluate complement activation via the lectin pathway as previously described (25,27). In brief, mouse serum, mannose-eluate, or GlcNAc-eluate was incubated on a GlcNAc-BSAcoated microtiter plate in 100 ml TBS-Ca at 37˚C for 10 min.…”
Section: Complement Activation Assaymentioning
confidence: 99%
“…However, their varied locations in assorted tissues and species are suggestive of their differential functions. Notably, the tissue distribution and function of the human M-ficolin and its homologue (ficolin b) in pigs (23) and mice (24) are substantially different (25). Hitherto, no consensus has been reached on the subcellular localization and fate of M-ficolin in human monocytes, whether intracellular in secretory granules (19,20), on the cell surface (18), or secreted into the serum (26), although the localization of M-ficolin in the neutrophils was recently reported (19).…”
mentioning
confidence: 99%